Gi-protein-coupled β1-adrenergic receptor: re-understanding the selectivity of β1-adrenergic receptor to G protein - Chen Hao; Zhang Suli; Hou Ruiqi; Liu Huirong (Acta Biochimica et Biophysica Sinica, 2022)
β1-adrenergic receptor (β1-AR), a member in the family of G-protein-coupled receptors, is a transmembrane receptor of great significance in the heart. Physiologically, catecholamines activate β1-AR to initiate a positive chronotropic, inotropic, and dromotropic change. It is believed that β1-AR couples to Gs protein and transmits the signal through second messenger cAMP. However, increasing research shows that β1-AR can also bind with Gi protein in addition to Gs. When β1-AR-Gi is biasedly activated, cardioprotective effects are introduced by the activated cGMP-protein kinase G (PKG) pathway and the transactivation of epidermal growth factor receptor (EGFR) pathway. The discovery of β1-AR-Gi signaling makes us reconsider the selectivity of G protein with regard to β1-AR, which also provides new ideas for the treatment of heart diseases. This review summarizes the discovery of β1-AR-Gi pathway, including the evidence that supports β1-AR’s capability to couple Gi, details of the transduction process and functions of the β1-AR-Gi signaling pathway.